Pathology - Gupta, Mary Elizabeth Peyton; Schneider, Arthur S. (Philadelphia, PA : Wolters Kluwer Health, 2021)
'This powerful, easy-to-use resource presents the essentials of pathology in the popular Board Review Series outline format that highlights the most tested topics for the USMLE Step 1'--
In process - PPUKM
Revised edition of: Pathology / Arthur S. Schneider, Philip A. Szanto. Fifth edition. [2014].
Includes index.
This book includes online access at http://thepoint.lww.com, please refer library staff for the password.
Keywords: Pathology -- Examinations, questions, etc; Examinations, questions